Relationship Between Neck Circumference and Epicardial Fat Thickness in a Healthy Male Population - Küçük,Uğur (2016)
Abstract Background: Epicardial fat is an upper body visceral fat depot that may play a significant role in the development of adverse metabolic and cardiovascular risk profiles. There is a significant direct relationship between the amount of epicardial fat and general body adiposity (body mass index, BMI), but data regarding subcutaneous adiposity is limited. Objective: We conducted a study to determine the association between neck circumference and epicardial fat thickness in healthy young male individuals, and assess their individual correlations with general body adiposity and cardiometabolic risk factors. Methods: One hundred consecutive male patients aged 18 years or older with no known major medical conditions were included in the study. All participants underwent detailed physical examination including measurement of blood pressure, weight, height, waist/hip ratio, and neck circumference. Blood was collected to determine fasting glucose and lipid parameters. A standard echocardiographic examination was performed with additional epicardial fat thickness determination. Results: Among 100 study participants, neck circumference correlated significantly with weight, waist circumference, BMI, blood glucose, serum total cholesterol, low-density (LDL)-cholesterol, and triglycerides levels. No significant correlation was found between neck circumference and high-density lipoprotein (HDL)-cholesterol levels. Neck circumference correlated moderately and positively with echocardiographic epicardial fat thickness. Conclusion: Among patients with low cardiometabolic risk, increased neck circumference was associated with increased epicardial fat thickness.